STUDENT'S SOLUTIONS MANUAL TO ACCOMPANY CALCULUS - Bradley Gerald L; Hoffmann Laurence D; Nichols Devilyna (Mcgraw Hill, 2007)
FUNCTIONS, GRAPHS AND LIMITS DIFFERENTIATION ADDITIONAL APPLICATIONS OF THE DERIVATIVE EXPONENTIAL AND LOGARITHMIC FUNCTIONS INTEGRATION
FUNCTIONS, GRAPHS AND LIMITS DIFFERENTIATION ADDITIONAL APPLICATIONS OF THE DERIVATIVE EXPONENTIAL AND LOGARITHMIC FUNCTIONS INTEGRATION